1959
DOI: 10.1002/hlca.19590420527
|View full text |Cite
|
Sign up to set email alerts
|

Die Synthese von Aldehyden und Ketonen mit Amidchloriden und VILSMEIER‐Reagenzien

Abstract: The constitution of amide chlorides and reaction products of amides with phosphoroxychloride is discussed. Based on infrared spectra and reaction behaviour an ionized constitution is proposed. The mechanism of VILSMEIER's aldehyde synthesis is studied. Under certain conditions this reaction can be extended to the synthesis of ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1968
1968
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…that the iminium chlorides themselves react similarly and Bosshard and Zollinger (43) have shown that comparable yields can be obtained using chlorodimethylformiminium chloride as the reagent. However, in the synthesis of diarylketones good yields are only obtained when the phosphorus oxychloride complex of the corresponding arylcarboxylic acid amide has been used (43). The synthesis of ketones from carboxylic acid amides, phosphorus oxychloride and suitable substrates predates the aldehyde synthesis by approximately 40 years e 53), but it is of only limited usefulness because side reactions are very often encountered e 07 ).…”
Section: Reaction With Nitrogen-hydrogen Bondsmentioning
confidence: 91%
See 2 more Smart Citations
“…that the iminium chlorides themselves react similarly and Bosshard and Zollinger (43) have shown that comparable yields can be obtained using chlorodimethylformiminium chloride as the reagent. However, in the synthesis of diarylketones good yields are only obtained when the phosphorus oxychloride complex of the corresponding arylcarboxylic acid amide has been used (43). The synthesis of ketones from carboxylic acid amides, phosphorus oxychloride and suitable substrates predates the aldehyde synthesis by approximately 40 years e 53), but it is of only limited usefulness because side reactions are very often encountered e 07 ).…”
Section: Reaction With Nitrogen-hydrogen Bondsmentioning
confidence: 91%
“…Since attack on nitrogen is not possible self-condensation via attack on carbon has been observed, and fJ-ketocarboxylic acid amides CXXVI are obtained in good yield (2,107,110). that the iminium chlorides themselves react similarly and Bosshard and Zollinger (43) have shown that comparable yields can be obtained using chlorodimethylformiminium chloride as the reagent. However, in the synthesis of diarylketones good yields are only obtained when the phosphorus oxychloride complex of the corresponding arylcarboxylic acid amide has been used (43).…”
Section: Reaction With Nitrogen-hydrogen Bondsmentioning
confidence: 93%
See 1 more Smart Citation
“…34 Dimethylformamide (DMF) has been found to catalyze the formation of acid chlorides with SOC1 2 . 35 At the same time, the possibility of the acid chloride reacting with DMF also exists. When a 20% solution of SOC1 2 in DMF was used, a violent reaction was activated by an initial period of heating.…”
Section: The Coupling Of Ethylenediamine To Peat Via An Acid Chloridementioning
confidence: 98%
“…VH reagents could be prepared form equimolar mixture of formamide or N, N'-dialkyl formamides such as N, N'-dimethyl formamide (DMF), N, N'-diethyl formamide (DEF), along with oxy halides such as POCl 3 and SOCl 2 at freezing temperatures. Recent reports on Vilsmeier-Haack (VH) reactions revealed that organic compounds in general and hydrocarbons with excess pi-electrons in particular undergo formylation very easily on synthetic scale [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. However, these reactions are known to afford acetyl derivatives when N, N'-dialkyl formamides are replaced by acetamide or N, N'-dialkyl acetamides such as N, N'-dimethyl acetamide (DMA) and N, N'-diethyl acetamide (DEA) in VH reagent.…”
Section: Introductionmentioning
confidence: 99%